Does 3D-speckle tracking echocardiography improve prediction of major cardiovascular events in a multi-ethnic general population? A Southall and Brent Revisited (SABRE) cohort study. - Lamia Al Saikhan; Chloe Park; Therese Tillin; Siana Jones; Jamil Mayet; Nish Chaturvedi; Alun Hughes (PLoS ONE)
3D-speckle tracking echocardiography(3D-STE) allows simultaneous assessment of ejection fraction(EF) and multidirectional strains, but its prognostic utility in the general population is unknown. We investigated if 3D-STE strains predicted a composite of major cardiac endpoints(MACE) beyond cardiovascular risk factors(CVDRF), and whether they were superior to 3D-EF. 529 participants in SABRE, a UK-based tri-ethnic general population cohort (69±6y; 76.6% male) with acceptable 3D-STE imaging were studied. Associations between 3D-EF or multidirectional myocardial strains and MACE(coronary heart disease(fatal/non-fatal), heart failure hospitalization, new-onset arrhythmia and cardiovascular mortality) were determined using Cox regression including adjustment for CVDRF and 2D-EF. Whether 3D-EF, global longitudinal strain(3D-GLS) and principle tangential strain(3D-PTS/3D-strain) improved cardiovascular risk stratification over CVDRF was investigated using a likelihood ratio test on a series of nested Cox proportional hazards models and Harrell's C statistics. During follow-up(median, 12y), there were 92 events. 3D-EF, 3D-GLS and 3D-PTS and 3D-RS were associated with MACE in unadjusted and models adjusted for CVDRF but not CVDRF+2D-EF. Compared to 3D-EF, both 3D-GLS and 3D-PTS slightly improved the predictive value over CVDRF for MACE, but the improvement was modest(C statistic increased from 0.698(0.647, 0.749) to 0.715(0.663, 0.766) comparing CVDRF with CVDRF +3D-GLS). 3D-STE-derived LV myocardial strains predicted MACE in a multi-ethnic general population sample of elderly individuals from the UK; however the added prognostic value of 3D-STE myocardial strains was small.